Education to increase knowledge of dental and oral health for the elderly at the Ikur Koto Community Health Center, Padang City - Erwin Setyawan; Tita Ratya Utari; Hanim Khalida Zia; Fajar Wahyu Triatmaja (Universitas Muhammadiyah Magelang, 2023)
The poor level of dental and oral health in the elderly can significantly impact their quality of life. Therefore, the purpose of this community service is to enhance the knowledge of dental and oral health among the elderly, ultimately improving their quality of life. The program utilized the talk show method, commencing with a pre-test and concluding with a post-test to assess the development of participants' knowledge. The results revealed a 36.67% increase in knowledge concerning dental and oral health in the elderly. This achievement is anticipated to contribute to the overall improvement in the quality of life for the elderly.